A Case of Focal Dermal Hypoplasia (Goltze Syndrome) Masquerading as Lingual Tonsillar Hypertrophy. (18th June 2019) - Roberts, Samuel T.; Shein, Greg; Jacobson, Ian
Abstract : Focal dermal hypoplasia is a rare condition affecting organ systems of mesodermal origin. We present a rare case of this condition presenting with apparent palatine tonsillar regrowth and outline our management. Airway management should always be a consideration in this rare condition.